The Influence of Family Environment on Children's Language Development - Siregar, Calvyn Sepanya; Damanik, Bernieke Anggita Ristia (Cahaya Ilmu Bangsa Institute, 2025)
The family environment plays a crucial role in shaping children's language development during their early years. This study explores the multifaceted impact of familial factors such as parental acquisition of language skills. Parental engagement in conversations, storytelling, and reading activities fosters vocabulary growth, grammatical understanding, and communication abilities. Socioeconomic disparities influence access to resources like books and educational opportunities, which directly affect language exposure and development. Additionally, a supportive and emotionally nurturing family environment enhances language acquisition by creating a positive context for learning. This research underscores the importance of fostering a language-rich and emotionally supportive home environment to promote optimal linguistic and cognitive development in children. Future interventions and policies aimed at addressing language delays must prioritize empowering families with resources and strategies for active engagement in their child's language learning journey.